richardson extrapolation method wrong
1 view (last 30 days)
Show older comments
Why is this richardson extrapolation method wrong?
function D=f_richardson(f,n,h,x0)
D=zeros(n,n);
e=zeros(n);
for t=1:n
D(1,t)=(f(x0+(2^(t-1))*h)-f(x0-(2^(t-1)*h)))/(2*((2^(t-1)*h)));
end
o=n-1;
for l=2:n
for k=1:o
D(l,k)=((2^(2*n-1))*D(l-1,k)-D(l-1,k+1))/(2^(2*n-1)-1);
end
o=o-1;
end
end
0 Comments
Answers (0)
See Also
Categories
Find more on Mathematics and Optimization in Help Center and File Exchange
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!